Exploring Ultrasonic Energy Followed by Natural Fermentation Processing to Enhance Functional Properties and Bioactive Compounds in Millet (Pennisetum glaucum L.) Grains - Mohammed Saeed Alkaltham; Akram A. Qasem; Mohamed A. Ibraheem; Amro B. Hassan (Fermentation)
This study explores the effect of ultrasonic treatment followed by fermentation on the in vitro protein digestibility, protein solubility, functional properties, antioxidant activity, total carotenoid content, and gamma-aminobutyric acid (GABA) levels in millet grains. Ultrasonic treatment was applied at different temperatures (20, 40, and 60 °C). The findings indicated significant improvements in phenolic and flavonoid contents and antioxidant activity in terms of the results of the DPPH, FRAP, and ABTS assays of millet grains after ultrasonic treatment alone or combined with fermentation. Moreover, the carotenoid and GABA contents were found to be significantly higher in the ultrasonic-treated grains. The protein solubility functional properties of the millet grains were also improved after the ultrasonic treatment alone or coupled with the fermentation process. Principal component analysis (PCA) revealed that the combined ultrasonic treatment and fermentation of the millet grains could enhance their antioxidant activity, functional characteristics, and vital compounds. Furthermore, the partial least squares (PLS) validation model emphasised that the ultrasonic treatment of millet at 40 °C, followed by fermentation, is the most optimal treatment among the other treatments. Hence, the conclusions highlight the potential of combined ultrasonic (40 °C) and fermentation treatments to improve grains’ nutritional value and functional properties, making millet more suitable for use in health-promoting food products.